Ansiedad y su influencia en las relaciones interpersonales de una persona de 20 años - Yepez Leon, Olga Elizabeth (2020)
The purpose of the case study is to determine the impact of generalized anxiety disorder on interpersonal relationships in a 20-year-old patient from the La Teresa campus of Febres Cordero parish in Los Ríos province. For this, theoretical and bibliographic research is used, which helps us to solve variables such as generalized anxiety disorder and interpersonal relationships, these variables are immersed in the subject of presentation and systematic methods are used with the help of some techniques and plans of corresponding treatment such as clinical interview, clinical history, Beck's anxiety inventory, Hamilton's anxiety scale, and psychometric test of social anxiety. It can help the patient diagnosed with generalized anxiety disorder F41.1 and with these techniques of the cognitive behavioral approach to improve the quality of life, the social and family environment, to achieve the desired results.